GE_GERICHTE C/21272/2008 vom 28. August 2015 - GE Cour de justice (2015)
DÉCISION D'IRRECEVABILITÉ; MODIFICATION DE LA DEMANDE; PRINCIPE DE LA CÉLÉRITÉ; CONNEXITÉ | aLPC.5; aLPC.133; CPC.308.1.a; CPC.308.2; CPC.404.1